Measuring child rhythm - Payne, E; Post, B; Astruc, L; Prieto, P; Vanrell, MDM (SAGE Publications, 2011)
Interval-based rhythm metrics were applied to the speech of English, Catalan and Spanish 2, 4 and 6 year-olds, and compared with the (adult-directed) speech of their mothers. Results reveal that child speech does not fall into a well-defined rhythmic class: for all three languages, it is more ‘vocalic’ (higher %V) than adult speech and has a tendency towards lower variability (when normalized for speech rate) in vocalic interval duration. Consonantal interval variability, however, is higher in child speech, particularly for younger children. Nevertheless, despite the identification of common, cross-linguistic patterns in child speech, the emergence of language-specific rhythmic indices is also clearly observable, even in the speech of 2 year-olds.